Uses and Gratifications Approach, Social Media and Personal Branding: A Study on Social Media Users in Turkey - Taşkıran, Hatun Boztepe (Communication Today, 2025)
The uses and gratifications approach has been an important part of communication studies for a long time, viewing target audiences not as passive recipients of messages disseminated via the communication processes but rather as active individuals who consciously consume media to satisfy their social or psychological needs. In older communication researches, the approach aimed to define the reasons why target audiences prefer certain kinds of ‘traditional’ media. However, it has recently been used in order to explore why people use social media (and to identify the needs people wish to satisfy by using them). The approach could also be used to explain whether (and how) people use social media to satisfy the recently popular need for personal branding. In light of the information mentioned above, the study deals with social media in relation to the uses and gratifications approach and analyses social media as a communication means able to gratify the need for personal branding. A total of 414 social media users in Turkey have answered a questionnaire. This quantitative research method has been designed for the research conducted as a part of the study. The data obtained from the research has shown that social media users in Turkey prefer to use social media to satisfy their needs of information seeking, social interaction, information sharing, passing time, entertainment, expressing opinions and relaxation and for convenience utility, communicatory usefulness and ‘surveillance’. Besides, it has been found out that many of the participants use social media for the purpose of personal branding.